MAKNA DAN FUNGSI KAIN ULOS PADA PUSAT LATIHAN OPERA BATAK PEMATANG SIANTAR (PLOt) DI PEMATANG SIANTAR PROVINSI SUMATERA UTARA - Enrico Alamo; Meria Eliza; Giat Syailillah (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
Ulos is a traditional Batak clothing that we can find in traditional events; birth, marriage, death and other Batak traditional ceremonies such as: Mandailing, Pakpak, Dairi, Sipirok-Angkola and Karo. Apart from being a typical cloth in the Batak community, Ulos is believed to be able to create a feeling of warmth and raise tondi (raga) because of the 'sacred' element inherent in Ulos. In the past, Ulos cloth was woven by 'spiritual' weavers using natural dyes. Ulos cloth is also a regional marker cloth; social level, and clan (surname). So not just any Ulos cloth can be given to someone or the community. Batak Opera Training Center (PLOt) Pematang Siantar. North Sumatra is one of the Ulos cloth user communities in every activity. The Batak Opera Group has undoubtedly existed until now. His performances reached many countries. The plays that are played also tell about the life of the Batak people and the epics of Batak heroism. The group's mission is to protect cultural heritage and develop traditional arts. For this reason, every stage of the PLOt is faithful in using hand-woven Ulos cloth. Judging from the patterns, colors and motifs of the Ulos fabrics used by PLOt, they seem